Effects of salicylic acid treatment on fruit quality and wax composition of blueberry (Vaccinium virgatum Ait). (30th January 2022) - Jiang, Bo; Liu, Ruiling; Fang, Xiangjun; Tong, Chuan; Chen, Hangjun; Gao, Haiyan
Highlights: Salicylic acid (SA) delayed blueberry fruit softening and deterioration. SA delayed declines of content of postharvest nutrient components. SA increased the wax triterpenoids in blueberry fruit. SA decayed the decrease of wax esters, sterols, fatty acids, alcohols, alkanes. Abstract: The cuticular wax layer in fruit is a hydrophobic barrier which protects fruit from biotic and abiotic stress. The cuticular wax also affect fruit quality. This paper investigated the effects of salicylic acid on fruit quality and the cuticular wax in blueberry fruit during storage at room temperature (25 °C). 'Powderblue' blueberries ( Vaccinium virgatum Ait) were treated with 1.0 mmol L -1 salicylic acid. The composition of cuticular wax layer and structure of epicuticular wax layer were analyzed at 4 d intervals during storage. Salicylic acid could efficiently delay the reduction of total wax content and affected the proportions of its constituents, including triterpenoids, esters, sterols, fatty acids, alcohols and alkanes. Our results also showed that there was no significant difference on the structure of epicuticular wax in salicylic acid treated fruits compared with that of the control. Salicylic acid delayed deterioration of blueberry fruit and enhanced its resistance to disease during storage.